The Symbol’s Brevity Rhetoric in Comparison with Metaphor and Allegory Based on Modern Poetry - Mohammad Ghaderimoghaddam; Raheleh Abdollahzadeh Borzo (مطالعات زبانی و بلاغی, 2018)
The brevity of modern poetry has emerged with new direction and different structures. Contemporary poets to make approach to symbolism as a factor for the development of brevity and compactness of art and with this artistic and rhetorical trick broaden the scope of their poem’s meaning. Then the disturbance and visual density away from their. Poems that it was a deficiency of the lyrics predecessors. In this paper, by studying brevity characteristics of symbol such as lack of symmetry, union of  pictures and thought ,immensity and  vague message, the nature of paradoxes, total reflection in the details, gloss and interpretation , we demonstrated symbolism in comparison with other types of imagery, in the concentrated expression and indirect is dedicated to the highest level.